ARE WAWO WORMS (Polychaeta, Annelida) UNIQUE TO MALUKU WATERS? - Joko Pamungkas; Alfiah Alfiah; Riena Prihandini (Masyarakat Zoologi Indonesia, 2021)
The natives of Ambon believe that wawo worms are unique to Maluku waters. The present study aimed to prove the presence of the animals outside of those areas. Samples were collected from the intertidal area of Barrang Lompo (South Sulawesi) and Bitung (North Sulawesi). We found two nereidid species identical to wawo species used to swarming in Maluku waters, i.e., Perinereis helleri (Grube, 1878) and P. nigropunctata (Horst, 1889), suggesting that the animals are not unique to Maluku waters and have a wider geographic distribution around the tropics. More taxonomic investigations are required to reveal the biodiversity of these poorly-studied marine creatures.